An Unusual Cardiomyopathy after Physical Stress in a Child. (10th January 2012) - Fabi, Marianna; Testa, Gabriella; Gesuete, Valentina; Balducci, Anna; Ragni, Luca
ABSTRACT Takotsubo cardiomyopathy, or broken heart syndrome, is characterized by transient left ventricular dysfunction associated to chest pain, elevation of cardiac enzymes, and electrocardiographic changes, mimicking an acute coronary syndrome, especially in older women after a physical or emotional stress. It is extremely infrequent in children as well as after infective stress. We described a celiac 4‐year‐old girl, following a gluten‐free diet, who developed features of cardiac failure few days after episodes of acute diarrhea with fever. The patient was treated with oral anticongestive therapy and intravenous immunoglobulins, and she had a dramatic and rapid improvement; echocardiographic features normalized in 48 hours.